I1SR Prabha and IISR Prathibha - two new high yielding and high quality turmeric (Curcuma longa L.) varieties - P N RAVINDRAN, B SASIKUMAR, JOHNSON K GEORGE, T JOHN ZACHARIAH, M J RATNAMBAL, K NIRMAL BABU, (Journal of Spices and Aromatic Crops, 1996)
IISR Prabha (Acc. 360) and IISR Prathibha (Acc. 361), developed at the Indian Institute of Spices Research, Calicut and recommended for release by the All India Coordinated Research Project on Spices are two valued added turmeric (Curcuma Zanga) varieties, developed for the first time through open pollinated progeny selection. These varieties surpassed most of the existing varieties including Alleppey in terms of curcumin content and oleoresin percentage. Maturing in 205 days under rainfed conditions, IISR Prabha has an average yield of 37.47 t/ha (fresh) with a dry recovery of 19.5 per cent, curcumin 6.52 per cent, oleoresin 15.0 per cent and essential oil 6.5 per cent. IISR Prathibha matures in about 225 days under rainfed conditions and has an average yield of 39.12 tlha (fresh) with a dry recovery of 18.9 per cent, curcumin 6.2 per cent, oleoresin 16.2 per cent and essential oil 6.2 per cent.